Controle genético da resistência à mancha angular e mapeamento de caracteres importantes no melhoramento do feijoeiro comum - Vieira, Gismar Silva (1997)
Angular leaf spot (Phaeoisariopsis griseola Sacc.) is a serious disease of common bean and its importance is increasing due to the short periods between cultivations. Resistance is the only practical mean for controlling this disease; however, the genetic control of the resistance reported in the literature has been fairly controversial, showing one to three genes, both dominant and/or recessive, conditioning this resistance. The objective of this investigation was to establish the genetic control of resistance to angular leaf spot in common bean. An F2 segregating population was obtained from a cross between a resisant Andean cultivar, AND 277, and a susceptible Middle American cultivar, Rosinha G2. The plant symptom severity as well as the pathogenecity and the pathogen origin were evaluated through the analysis of symptoms of 46 inoculated cultivars. Inoculations consisted of 2x104 spores/ml and were applied in the evening. Inoculated plants remained in the dark for 48 hours with high humidity (>90%). The pathogen was classified as of Middle American origin. Chi-square data of symptom severity in the F2 population demonstrated that resistancee is conditioned by one gene with complete dominance and no maternal effects. The cv. AND 277 is completely resistant to the angular leaf spot Middle American strain, and also does not present genetic incompatibility in crosses with Middle American cultivars.